Gabon: Recent developments in agricultural research - Stads, Gert-Jan; Angwe, Paul Obiang (International Food Policy Research Institute, 2011)
Agriculture in Gabon has traditionally been overshadowed by more attractive economic sectors such as forest exploitation, mining, and oil extraction. As a result, agricultural research and development (R&D) spending and capacity levels have remained low compared with other African countries. However, as a response to dwindling natural resource reserves in the mining and oil sectors, agriculture has recently gained prominence (Stads, Obiang Angwe, and Ngoye 2004).